Real-world Biapenem vs. Meropenem in the treatment of severe community-acquired pneumonia in children: A propensity score matching analysis - Tao, Xuemei; Xu, Changjing; Zhong, Xiaoyan; Mou, Yao; Li, Jingwei; Yang, Xuping; Huang, Yilan (Frontiers in Pediatrics, 2022)
Objective To compare the real-world efficacy and safety of Biapenem and Meropenem for treating severe community-acquired pneumonia (SCAP) in children. Methods We retrospectively evaluated 915 children with SCAP who were treated with Biapenem or Meropenem from August 2018 to June 2022. A 1:1 propensity score matching (PSM) analysis was used to reduce the actual baseline difference between groups. Results 416 patients participated in the analysis after PSM (Biapenem: Meropenem = 1:1). For the Biapenem group and Meropenem group, the effective rates were 90.4% and 90.9%, respectively (p = 1.0) and the incidence of adverse reactions were 7.7% and 7.2%, respectively (p = 1.0). There were no statistical differences between Biapenem and Meropenem. Conclusion In general, the efficacy and safety of Biapenem are comparable to Meropenem in the treatment of children with SCAP.